Pengawetan Kayu Pulai (Alstonia scholaris L.) Dengan Asap Cair Ampas Tebu Terhadap Serangan Hama Rayap Tanah (Coptotermes curvignathus Holmgren.) - Andrie Andrie; Rudianda Sulaeman; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Pulai wood’s is used for produce any products and we can find it easily also it is able to be influenced in critical field, while durable grade is V and powerful class is IV-V and it is low-grade durable, because of that it is needed preservation on pulai wood. Many preservation using chemicals that are harmful to environment and humans. In utilizing natural ingredients derived from plants as safer alternative preservatives for environment and humans, it can be renewable for preserving wood from invading organisms wood destroying, especially termites. Material used as a preservative is liquid smoke empty baggase. The aims of this research are to determine termite mortality, retention and weight lose as well as know the effectiveness of giving liquid smoke on pulai wood preservation against termite attack. The methods used in this research is Randomized Complete Design, the concentration of liquid smoke baggase of 0%, 10%, 20% and 30% with 5 replication for 6 weeks is fed on termites. The results showed that using of preservatives smoke liquid at concentration of 30% has a value of lose weight on pulai wood of 10,57%/cm3, 100% termite mortality and retention of 5.57%.Key word: Liquid smoke, baggase, preservative, pulai wood and Coptotermes curvignathus Holmgren.